A STUDY OF ALEXIA FOUND IN THE BOOK THE MAN WHO FORGOT HOW TO READ: TRUE STORY - ADHITARA, AGIESTA WIDYANTI (Jurnal Ilmiah Mahasiswa FIB, 2013)
This research is designed to find out characteristics of alexia shown by Howard Engel as an alexic (alexia patient) and to find out the patterns of reading difficulties shown by him. This research used a document/textual analysis approach. There are two data in this study, the primary data is sentences/narration taken from the book The Man Who Forgot How to Read: True Story and the secondary data is utterances taken from the video entitled Alexia sin agrafia:. The researcher collaborated with Prof. Alexander Howard Engel (Oliver Sacks) P. Leff as the expert validator and had the discussion via e-mail.The researcher used the theory of Leff and Schofield (2010) and Mize (2013). The results of this research show that there are seven characteristics of alexia and seven patterns of reading difficulties. Seven characteristics that are shown by Howard Engel as the patient of alexia are (1) he cannot read or recognize either printed or written form, (2) his right visual field is not intact, (3) he has problems with letter identity, (4) he has problems with memory, (5) he has difficulties in processing numbers or non-linguistic stimuli, (6) he experiences difficulty in reading as word length increases (word-length effect), but (7) he still can write. Seven patterns of reading difficulties that are shown by him are (1) having difficulty in relating letters and sound, (2) having difficulty in recognizing consistent patterns, (3) having slow rate of decoding, (4) having to apply decoding strategies to recognize the whole words, (5) having slow speed reading and comprehension falters, (6) having an ability to fluently identify words, and (7) having lack workable strategies for comprehending and remembering what he read.Some suggestions are made for the next researchers to explore and investigate more about patients of alexia in the real life. Moreover, the next researchers can analyze the alexia phenomena by using other theories. Key words : Psycholinguistics, Alexia, Reading Difficulty